2013
DOI: 10.1002/btpr.1667
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of exogenous siRNA addition as a metabolic engineering tool for modifying biopharmaceuticals

Abstract: Traditional metabolic engineering approaches, including homologous recombination, zinc finger nucleases, and short hairpin RNA (shRNA), have previously been employed to generate biologics with specific characteristics that improve efficacy, potency, and safety. An alternative approach is to exogenously add soluble small interfering RNA (siRNA) duplexes, formulated with a cationic lipid, directly to cells grown in shake flasks or bioreactors, This approach has the following potential advantages : no cell line d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Five milliliters of each sample was then centrifuged at 1,000 rpm to pellet the cells, with the pellet stored at −80 °C until needed. Prior to conducting this study, CHO‐DG44 cells were stably transfected with a previously reported plasmid vector containing an anti‐CD20 mAb gene sequence (bioreactor studies) or an empty plasmid vector without no transgene expressed (proteomic studies) containing the DHFR gene controlled by a cytomegalovirus promoter. Viable cell densities (VCDs) were measured using a Multisizer Coulter Counter (Beckman Coulter, Fullerton, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Five milliliters of each sample was then centrifuged at 1,000 rpm to pellet the cells, with the pellet stored at −80 °C until needed. Prior to conducting this study, CHO‐DG44 cells were stably transfected with a previously reported plasmid vector containing an anti‐CD20 mAb gene sequence (bioreactor studies) or an empty plasmid vector without no transgene expressed (proteomic studies) containing the DHFR gene controlled by a cytomegalovirus promoter. Viable cell densities (VCDs) were measured using a Multisizer Coulter Counter (Beckman Coulter, Fullerton, CA).…”
Section: Methodsmentioning
confidence: 99%
“…RNAi-mediated mAb was manufactured at Alnylam Pharmaceuticals and provided as 1 mg/mL × 0.8 mL as previously described. 12 Rituximab was purchased by Alnylam from Imperial College, London and provided as 10 mg/mL × 0.5 mL. The samples were aliquoted as 10 μL per vial for rituximab (100 μg) and 100 μL per vial for RNAi-mediated mAb (100 μg) and stored at −80°C before analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The reduction of the core fucose induced a 17-fold improvement in FcγRIIIa binding, and an increase in specific cell lysis by up to 30%, as determined in an ADCC assay. 12 Other modifications. MAbs with "Q" or "E" N-terminal amino acids could easily convert to pyro-Glu.…”
Section: Fc Glycosylationmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of a transient approach using synthetic siRNA include the ability to outsource production and the fact that multiple siRNA constructs can be generated in a fraction of the time taken to generate constructs in plasmids. Furthermore, synthetic siRNA is efficacious, as evidenced by literature examples of Fut8 gene silencing that are sufficient to reduce FUT8 protein expression 25 and yield afucosylated IgGs with increased FCgRIIIa binding and ADCC 26 .…”
Section: Introductionmentioning
confidence: 99%